2018
DOI: 10.1093/glycob/cwy096
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of fucosyltransferase (FUT) genes using the CRISPR-dCas9-VPR technology reveals potent N-glycome alterations in colorectal cancer cells

Abstract: Aberrant fucosylation in cancer cells is considered as a signature of malignant cell transformation and it is associated with tumor progression, metastasis and resistance to chemotherapy. Specifically, in colorectal cancer cells, increased levels of the fucosylated Lewisx antigen are attributed to the deregulated expression of pertinent fucosyltransferases, like fucosyltransferase 4 (FUT4) and fucosyltransferase 9 (FUT9). However, the lack of experimental models closely mimicking cancer-specific regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Fucosylation is an important functional regulation of glycoproteins and is critical for the abnormal glycosylation during tumor progression. FUT4 is abnormally upregulated in different types of cancers, such as colorectal cancer [19], breast cancer [20] and lung adenocarcinoma [21], and the up-regulation of FUT4 is associated with tumor metastases, higher recurrence, and poorer survival in tumor patients. According to these findings, we speculate that FUT4 is a key factor in promoting malignant progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Fucosylation is an important functional regulation of glycoproteins and is critical for the abnormal glycosylation during tumor progression. FUT4 is abnormally upregulated in different types of cancers, such as colorectal cancer [19], breast cancer [20] and lung adenocarcinoma [21], and the up-regulation of FUT4 is associated with tumor metastases, higher recurrence, and poorer survival in tumor patients. According to these findings, we speculate that FUT4 is a key factor in promoting malignant progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…FUT family is a class of glycosyltransferase molecules that are involved in the synthesis of glycoproteins and glycolipid sugar chains on the cell surface, which play important role in a variety of physiological processes. 19 The FUT family can be divided into four subfamilies according to the different transferase activities. FUT4 is a key enzyme for the synthesis of sialylated Lewis oligosaccharide X (SLeX), and the previous study showed that abnormal expression of FUT4 has important links with tumorigenesis, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were vortexed and then incubated overnight at 37 °C. The released glycans were then converted to aldoses with 0.1% formic acid, filtered through a protein‐binding membrane, and dried . Released N ‐glycans were fluorescently labelled by reductive amination with procainamide using LudgerTag Procainamide Glycan Labelling Kit (LT‐KPROC‐24) as described previously…”
Section: Methodsmentioning
confidence: 99%
“…Procainamide‐labelled N ‐glycan samples and system suitability standards were analyzed by HILIC‐(U)HPLC‐ESI‐MS with fluorescence detection, using the previously described protocol . Relative glycan quantification was achieved using HappyTools software, allowing automated peak, background, and noise detection .…”
Section: Methodsmentioning
confidence: 99%